Superiority of capsaicin 8% patch versus oral pregabalin on dynamic mechanical allodynia in patients with peripheral neuropathic pain - Cruccu, G. (Eur J Pain, 2017)
BACKGROUND: Dynamic Mechanical Allodynia (DMA) is a typical symptom of neuropathic pain (NP). In a recent study, the capsaicin 8% patch was noninferior to pregabalin in overall peripheral NP relief. In this study, we report the comparison of the two treatments in relieving DMA. METHODS: In a randomized, open‐label, head‐to‐head, 8‐week study, 488 patients with peripheral NP were treated with the capsaicin 8% patch (one application) or an optimized dose of pregabalin. Assessments included the area and intensity of DMA, and the number of patients achieving complete resolution of DMA. RESULTS: At baseline, 253 patients in the capsaicin 8% patch group and 235 patients in the pregabalin group had DMA. From baseline to end of study, the change in DMA intensity was significantly in favour of the capsaicin 8% patch versus pregabalin [−0.63 (95% CI: −1.04, −0.23; p = 0.002)]. Similarly, the capsaicin 8% patch was superior to pregabalin in reducing the area of DMA [−39.5 cm(2) (95% CI: −69.1, −10.0; p = 0.009)] from baseline to end of study. Overall, a greater proportion of patients had a complete resolution of allodynia with capsaicin 8% patch treatment compared with pregabalin treatment (24.1% vs. 12.3%; p = 0.001) at end of study. CONCLUSION: Capsaicin 8% treatment was superior to pregabalin in reducing the intensity and area of DMA, and in the number of patients with complete resolution of DMA. SIGNIFICANCE: The superiority of a topical treatment over pregabalin in relieving DMA supports the view that both peripheral and central sensitization can mediate allodynia.